Effect of Type and Arbuskular Mikoriza Mushroom Dosage (CMA) to Growth of Chili [Capsicum annuum L.] at Ultisol Soil - Harlis, Harlis; Murni, Pinta; Fitria, Ayu Billy (Universitas Jambi, 2008)
The research has objective to know the effect of type and arbuskular mikoriza mushroom doses (CMA)to growth of chili (Capsicum annuum L.) at ultisol soil. This research used Completely Randomize Design of Factorialpattern consisting of two factor, that is : first factor of mikoriza type which consist of 3 level, j1 = Glomus sp., j2 =Gigaspora sp. and j3 = Glomus sp. and Gigaspora sp., than second factor of mikoriza doses which consist of 4level, d0 = 0 g, d1 = 5 g, d2 = 10 g. and d3 = 15 g. Data analyzed to use ANOVA and test continued DNMRT at 5% reallevel. The result showed that arbiskular mikoriza doses and type was significantly different to high plant, biomass growon and content of P. Type Gigaspora sp. with dose 15 g can be improve P element absorption and optimal growthvegetative.